Peer support for parents of disabled children part 2: how organizational and process factors influenced shared experience in a one‐to‐one service, a qualitative study. (2nd January 2015) - Shilling, V.; Bailey, S.; Logan, S.; Morris, C.
Abstract Background Parents of disabled children often seek support from their peers. The shared experience between parents appears to be a crucial mediating factor. Understanding how a sense of shared experience is fostered can help to design and evaluate services that seek to provide peer support. Methods We carried out a qualitative study involving semi‐structured interviews and focus groups. Participants were 12 parents and 23 befrienders who had contact with the Face2Face one‐to‐one befriending service in Devon and Cornwall during a 12‐month period, and 10 professionals from health, social care and education. Findings Formal structures and processes in place such as training and ongoing supervision and support were highly valued as was the highly personalized, confidential, flexible, one‐to‐one at‐home nature of the service. Crucial to establishing rapport was putting the right people together and ensuring a good match between befrienders and parents. Clearly, the befriending parent has to be emotionally prepared to provide help. However, if the parent being offered support was not ready to accept help at the time it was offered or the type of support was not right for them, they are less likely to engage with the service. Conclusion Organizational and process factors as well as characteristics of the parents offering and receiving support contribute to the sense of shared experience in one‐to‐one peer support. These factors interact to influence whether peer support is effective and should be explicitly considered when designing and evaluating services.